The Simple View of Reading in Children Acquiring a Regular Orthography (Italian): A Network Analysis Approach - Angelelli, Paola; Romano, Daniele Luigi; Marinelli, Chiara Valeria; Macchitella, Luigi; Zoccolotti, Pierluigi (Frontiers in Psychology, 2021)
In the present study, we explored the unique contribution of reading accuracy, reading fluency, and linguistic comprehension, within the frame of Simple View of Reading (SVR), in a sample of 118 3rd to 5th grade children learning Italian, a language with a highly regular orthography. We adopted a flexible method of analysis, the Network Analysis (NA), particularly suited for exploring relations among different domains, where the direct relations between a set of variables intercorrelated with one another is the core interest. Results indicated an independent and unique contribution of syntactic comprehension skills on the one hand and of both reading fluency and reading accuracy on the other to the comprehension of a written text. The decoding measures were not directly associated with non-verbal reasoning, nor the latter was directly associated with reading comprehension, while it was strongly related to oral syntactic comprehension. Overall, the pattern of findings is broadly consistent with the predictions of SVR and underscores how, in an orthographically regular language, not only oral comprehension skills but also reading fluency and reading accuracy directly influence reading comprehension. Data are discussed in a cross-linguistic perspective. Implications for educational and rehabilitative purposes are also presented.